Two-Country Dynamic Model of Trade with Heterogeneous Firms and Comparative Advantage - Wolfgang Lechthaler; Mariya Mileva (WWWforEurope, 2013)
We develop a dynamic trade model with comparative advantage, heterogeneous firms and workers and endogenous firm entry to study wage inequality during the adjustment to trade liberalization. We find that trade liberalization increases wage inequality both in the short run and in the long run. In the short run, wage inequality is mainly driven by inter-sectoral wage inequality, while in the long run, wage inequality is driven by an increase in the skill premium. It is not a good idea to exclude certain sectors from trade liberalization, because that greatly reduces the benefits of trade liberalization, while failing to protect vulnerable workers.
Keywords: E24; F11; F16; J62; 330; Trade liberalization; wage inequality; adjustment dynamics